This might be one way to do it. Start with point-slope form y = m(x - x1) + y1 y = m*x - m*x1 + y1 -m*x + y = -m*x1 + y1

**m*x + y = m*x1 - y1**If m, x1, y1 are positive integers, this is standard form. Otherwise, the equation needs to be multiplied by the LCM of the denominators of the fractions, and the signs adjusted so that the coefficient of x is positive.__Example__Slope = -1/3, point = (1/3, 3/4) Using the above formula, we have (-1/3)x + y = (-1/3)(1/3) - 3/4 Multiplying this by -36 gives 12x - 36y = 4 + 27**12x - 36y = 31**(standard form)